HIV and Hepatitis B seroprevalence among the nepalese blood donors - Kandel, SR; Ghimire, P; Tiwari, BR; Rajkarnikar, M (Journal of Pathology of Nepal, 2013)
Background: HIV and Hepatitis B infections are public health problems in Nepal. This study was conducted based at NRCS/CBTS, with the objective of determining the HIV and HBsAg sero-prevalence in non-remunerated volunteer blood donors. Materials and Methods: A total of 66,904 units of blood collected, following donor recruitment criteriaduring March 2009-Sept. 2010 was included for analysis. All donated blood samples were subjected to screening for Transfusion transmitted infections including HIV and Hepatitis B surface antigen using standard ELISA test kits (Dade Behring, Germany). Initial reactive sera were re-tested for reconfi rmation with same test kits plus another test kit (Detect-HIV, Adaltis Inc, and Qualisa). Results: Out of 66,904 units of blood collected, 56,973 units were from male and 9,931 were from female donors. Among the total screened samples, 73 (0.10%) were found to be positive for HIV, 0.11% (64/56973) in male and 0.09% (9/9931) in female; the difference between male and female donors (?2<3.841) was statistically signifi cant. The seroprevalence of HIV was highest in age group of 30- 39 both in male and female (p<0.001). Similarly, for HBsAg, overall seroprevalence was found to be 0.47% (316/66904 0.42% (242/56973) in male and 0.74% (74/9931) in female. The difference was statistically signifi cant (?2<3.841). The highest HBsAg sero-prevalence(0.65%) was also observed in same age group i.e. 30-39 (p<0.001) in male but highest seroprevalence (2.63%) was observed inage group of ?50 in female. Conclusion: Both HIV and HBV sero-prevalence is high in adult voluntary blood donors. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 390-393 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7864